Effect of fibre loading on the microstructural, electrical, and mechanical properties of carbon fibre incorporated smart cement-based composites - Zhang, Jiacheng; Heath, Andrew; Ball, Richard J.; Paine, Kevin (Frontiers in Materials, 2022)
Carbon fibre reinforced self-sensing cement-based sensors offer a potential low-cost solution to the multi-purpose health monitoring of concrete structures. This paper presents the transitional pro-cesses of the microstructural, electrical, and mechanical behaviours of cement-based sensors incorporating chopped carbon fibres from low dosages at 0 – 0.1% by volume (vol.%) with detailed intervals, to high dosages up to 2.4 vol.%. In comparison to the plain mortar, cement-based sensors at all fibre contents had higher flexural strength, whereas the compressive strength was higher up to fibre contents of 1.0 vol.% but lower with further increases in fibre content. No significant improvement of compressive strength was observed at low fibre contents 0 – 0.1 vol.%. The peak mechanical performance was found at fibre contents of 0.2 – 0.3 vol.%. The bulk conductivity of cement-based sensors underwent a double percolation process where the percolation zone of the fibres was identified at fibre contents of 0 – 0.1 vol.% and the percolation zone of the capillary pores resided at fibre contents of 2.1 – 2.4 vol.%. This study is a necessary step prior to the assessment of self-sensing performance of cement-based sensors. A selection of desired physical properties can be done by referring to the transitional processes in this fundamental research achieving the multifunctionality of in-situ self-sensing.